IMPLEMENTASI PROGRAM JAMINAN SOSIAL KETENAGAKERJAAN DI KOTA MANADO - Ginting, Anna Feberina; Dengo, Salmin; Kolondam, Helly F (JURNAL ADMINISTRASI PUBLIK, 2016)
The Social Security National is a system of the implementation of the country andthe government to provide social protection, so that each of the population meet the basicneeds of the life, to the realization of social welfare for the entire population of Indonesia.The type of the social security encompasses health insurance, guarantee the accident, death,the old days, retirement. Implementation of the 5 (five) programs of social security in thesocial security system of national is expected to reach membership of the labor force arewidely an ongoing basis, so that the people can meet basic needs as well as a guarantee ofliving either working in the formal and informal. The program guarantees social employmentbe seen from 4 of the implementation according to Edward III that is communication,resources, disposisi, and the structure of bureaucracy.The research is using the method of approach to a qualitative descriptive through indepthinterviews to the 10 people was an informer. Observation and the additionaldocuments in the form of a list of guidelines for the interview, tape recorder, and the paper.The result showed that in general the implementation of the guarantee of employmentis not good.Keyword: Implementation of labor social security program